Exploring Students’ Perceptions of Digital Media Use in English Language - Yusuf, Nur Laili; Yusuf, Nur Laili yusuf (Mastery: Master of English Language Journal, 2025)
This study aims to understand how learners view the role of digital platforms such as YouTube, online dictionaries, and learning applications, in enhancing their English skills. The qualitative method used in this study. Data were collected through semi- structured interviews with SMK Al-Maliki students who actively use digital media for learning English. Participants were selected through purposive sampling. The findings reveal that digital media increases students’ motivation and engagement; it provides access to authentic English exposure; it promotes both collaborative and independent learning; and there were some challenges arise due to unstable internet and distractions. The study concludes that digital media positively influences students’ engagement and English learning experiences when used effectively. However, successful implementation requires balanced teacher guidance, adequate infrastructure, and learner self-discipline. The study suggests that integrating digital tools strategically can create more interactive, autonomous, and meaningful EFL learning experiences.